(untitled) (Academicia Globe: Inderscience Research, 2021)
This article is about enriching your English vocabulary. It examines the problems of memorization, learning new words in English, and also addresses problems, obstacles, arising in the process of mastering vocabulary. Suggests methods and techniques of learning, memorizing new words.